KONTRIBUSI LINGKUNGAN SEKOLAH DAN KOMPETENSI GURU TERHADAP HASIL BELAJAR GEOGRAFI SISWA SMA NEGERI 1 SATUI - Rini Desterianti (Universitas Lambung Mangkurat, 2016)
The purposes of this research were: (1) to find out the contributions of the school environment partially towards the geography learning outcomes of the students of SMAN 1 Satui. (2) to find out the contribution of teacher competence partially towards the geography learning outcomes of the students of SMAN 1 Satui; (3) to find out the contributions of school environment and teacher competence towards the Geography learning outcomes of the students of SMAN 1 Satui. The method in this study used survey method with a quantitative research approach. Samples were taken by using proportional stratified random sampling of 201 students of class XI and XII majoring in social studies. From the population, 67 students were selected as the study samples. The research found: (1) t count> t table (6.002> 1.998) means that the school environment partially contributes to geography learning outcomes of students, (2) the value of t count> t table (2.120> 1.988) means that the competence of teachers partially contributes to the geography learning outcomes of students; (3) F count> F table (28.320> 3.991) means that the school environment and teacher competence simultaneously affect positively and contribute to the geography learning outcomes of the students of SMAN 1 Satui; (4) Adjusted R Square was 0.453 or (45.30%). The conclusion of this study, namely: (1) the school environment partially contributed to the geography learning outcomes of the students of SMAN 1 Satui, t value was positive which means if the school environment is better, it will further enhance the geography learning outcomes of the students of SMAN 1 Satui; (2) teacher competence partially contributed to the geography learning outcomes of the students of SMAN 1 Satui, t value was positive which means the better the competence of the teachers and the more increase the geography learning outcomes of the students of SMAN 1 Satui (3) The school environment and teacher competence jointly contributed to the geography learning outcomes of the students of SMAN 1 Satui.Keywords: contributions, school environment, teacher competence, learning outcomes, Geography Tujuan dari penelitian ini adalah: (1) untuk mengetahui kontribusi dari lingkungan sekolah secara parsial terhadap hasil belajar geografi siswa dari SMAN 1 Satui. (2) untuk mengetahui kontribusi kompetensi guru secara parsial terhadap hasil belajar geografi siswa dari SMAN 1 Satui; (3) untuk mengetahui kontribusi dari lingkungan sekolah dan kompetensi guru terhadap hasil belajar Geografi siswa dari SMAN 1 Satui. Metode dalam penelitian ini menggunakan metode survei dengan pendekatan penelitian kuantitatif. Sampel diambil dengan menggunakan proporsional stratified random sampling dari 201 siswa dari kelas XI dan XII jurusan IPS. Dari populasi, 67 siswa terpilih sebagai sampel penelitian. Penelitian menemukan: (1) t hitung> t tabel (6,002> 1,998) berarti bahwa lingkungan sekolah sebagian kontribusi untuk geografi hasil belajar siswa, (2) nilai t hitung> t tabel (2,120> 1,988) berarti bahwa kompetensi guru sebagian kontribusi terhadap hasil belajar geografi siswa; (3) F hitung> F tabel (28,320> 3,991) berarti bahwa lingkungan sekolah dan kompetensi guru secara simultan berpengaruh positif dan berkontribusi terhadap hasil belajar geografi siswa dari SMAN 1 Satui; (4) Adjusted R Square adalah 0,453 atau (45,30%). Kesimpulan dari penelitian ini, yaitu: (1) lingkungan sekolah sebagian kontribusi terhadap hasil belajar geografi siswa dari SMAN 1 Satui, nilai t adalah positif yang berarti jika lingkungan sekolah lebih baik, itu akan lebih meningkatkan hasil belajar geografi siswa dari SMAN 1 Satui; (2) kompetensi guru secara parsial memberikan kontribusi terhadap hasil belajar geografi siswa dari SMAN 1 Satui, nilai t adalah positif yang berarti semakin baik kompetensi guru dan lebih meningkatkan hasil belajar geografi siswa dari SMAN 1 Satui (3 ) lingkungan sekolah dan kompetensi guru secara bersama-sama memberikan kontribusi terhadap hasil belajar geografi siswa dari SMAN 1 Satui.Kata kunci: kontribusi, lingkungan sekolah, kompetensi guru, hasil belajar, Geografi